Implementation of Pancasila Values in Character Education: A Literature Review - Natalia, Veronica Eka Desi; Pratama, Anisa OS; Astuti, Margareta Dewi (Universitas Pendidikan Indonesia (UPI), 2021)
The implementation of Pancasila values in character education is very important and interesting to discuss. There are a number of articles related to the implementation of Pancasila values in character education but there is still little literature on the literature review. The purpose of writing this article is to identify and identify the implementation of Pancasila values in strengthening character education as a literature review. Based on the literature review, it is known that the implementation of Pancasila values is very important in relation to character education. Characters that are appropriate and are shown attitudes related to the values contained in Pancasila, namely the values of character divine values (religious), love for the country, independence, environmental care and tolerance .